PENGEMBANGAN PRODUK KAMPUNG BAMBOO SEBAGAI DAYA TARIK WISATA OUTBOUND BERBASIS EXPERIENTIAL LEARNING DI DESA CIMENYAN KABUPATEN BANDUNG - Amanda, Detha (2015)
Kampung Bamboo merupakandayatarikwisataoutbound yang ada di KecamatanCimenyanKabupaten Bandung.Kampung Bamboo sebagaidayatarikwisataoutboundbelummenerapkankonsepexperiential learningdenganbaik, danbelummenyesuaikanMisiKampung Bamboo kedalam program yang ada.Experiential learningmerupakankonsepoutbounddengantahapanpembelajaranyaitu :concrete experience, reflective observation, abstract conceptualization, dan active experimentation, agar wisataoutboundtidakhanyakegiatanfuntapiterdapatpembelajaran yang bermanfaatbagipengembangandiridansoft skillspesertanya. Penelitianinimenggunakanmetodekualitatif, sedangkandesainpenelitianinimenggunakandesainpenelitian Gold (1980) terdiridaritigatahapan: inventarisasi, analisis, sintesisuntukmemudahkanpenelitidalammengembangkanprodukwisataoutboundberbasisexperiential learning. Dalampenelitianinimenggunakanmetodewawancara, danpenyebarankuesioneruntukmengumpulkan data sebelumdiolahmenjadibentukdeskriptif.Berdasarkanhasilpenelitian, penelitimenyimpulkanbahwaprodukwisataKampung Bamboo belummenerapkanexperiential learningdankendaladalampengembanganproduktersebutterbagikedalamaspekwawasanatauketerampilansumberdayamanusia, danmanajemenataupengelola yang bersikapapatistidakmaumenjalinkerjasamadenganpihakterkaitsehinggamengalamikesulitanbiayaoperasional, pengembanganproduk, danpromosi. Kampung Bamboo dapatmengembangkanprodukwisataoutboundberbasisexperiential learningdengan lima level produkyaitu :produkinti, produkdasar, produk yang diharapkan, produktambahan, danprodukpotensialsehinggaKampung Bamboo menjadidayatarikwisataoutboundunggulan. Kata Kunci :PengembanganProdukWisata, Experiential Learning, Outbound Kampung Bamboo is an outbound tourist attraction located in Cimenyan, Bandung Regency. Kampung Bamboo as an outbound tourist attraction has not apply the experiential learning concept rightly, and has not adjust its missions to the existing programs yet. Experiential learning is an outbound concept with some additional learnings such as: concrete experience, reflective observation, abstract conceptualization, and active experimentation so that tourist do not only have fun, but also get a useful learning to develop themselves and their soft skills. This research used a qualitative approach, while the design is based on Gold Research Design (1980), consisting three steps: inventorying, analysis and synthesis to help developing the outbound product based on experiential learning. This research used interview and questionnaires to get the data before being processed into descriptive form. Based on the research, the experiential learning has not been applied into Kampung Bamboo product, and the obstacles in developing those products are the human resource's skill and the apathetic management who does not want to cooperate with other stakeholders so it faces a budgeting problem for operational, product development and promotion. Kampung Bamboo could develop the outbound tourist attraction based on experiential learning with five levels of product: core product, basic product, expected product, additional product and potential product so it becomes a leading tourist attraction in outbound. Keywords: Tourism Product Development, Experiential Learning, Outbound